Inclusive Growth Effects of Institutional Quality in Nigeria - Olanrewaju, Gideon O.; Aremo, Adeleke Gabriel; Binuyo, Babatunde O. (European Scientific Journal, ESJ, 2020)
This study empirically examined the relationships between institutional quality and inclusive growth as measured by the real GDP per person employed (RGDPE) in Nigeria. An Autoregressive Distributed Lag (ARDL) Boundstesting approach to cointegration was employed using annual secondary time series data from 1998 to 2017. The data were sourced from the Central Bank of Nigeria’s statistical Bulletin, National Bureau of Statistics’ final Accounts, IMF’s International Financial Statistics (IFS) and Worldwide Governance Indicators (WGIs). The study concluded that institutional quality had a significant effect on inclusive growth in Nigeria. It is therefore recommended that institutional improvement beyond the present liberal democratic threshold is much needed to effectively harness the human capital resource base. The Nigerian government should adopt a labour-intensive development strategy such that poor active households are comprehensively integrated into productive activities for optimal value-chain finance-growth inclusiveness. This would address the protracted tripartite socio-economic problems of poverty, inequality and unemployment in line with Lin’s comparative advantage conforming hypothesis. e. This would enhance formulating and implementing employment growth-oriented policies that are compatible with the society’s resources endowment and developmental goals.